Across the Board: Mark Mascal on the Challenges of Lignin Biorefining. Issue 1 (3rd December 2019) - Mascal, Mark
Abstract: In this series of articles, the board members of ChemSusChem discuss recent research articles that they consider of exceptional quality and importance for sustainability. This entry features Prof. M. Mascal, who describes some creative solutions to the challenge of lignin biorefining and shares thoughts about how the purposes of sustainability are best served. Topics discussed include lignin saturation and hydrodeoxygenation, lignin isolation, a lignin to muconic acid pathway, and the production of 2, 4‐ and 2, 5‐pyrinedicarboxylic acids from lignin. Abstract : The final frontier : Our board member Prof. Mark Mascal discusses creative solutions for lignin biorefining as well as how to best serve the purposes of sustainability. Examples include lignin saturation and hydrodeoxygenation, lignin isolation, and lignin to muconic acid and pyridinedicarboxylic acid pathways.